SENSORY EVALUATION AND CHARACTERIZATIONS OF EMULSION CONTAINING SODIUM CHLORIDE AND ITS APPLICATION IN CORN SOUP - Melanie Cornelia; Irene Triyanti; Teguh Prasetia; Cathy Purnomo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Reduction of sodium chloride in food products has been reported to lower consumers’ acceptance. In this research, the physical characteristics and sensory property of an oil in water emulsion containing sodium chloride, as well as its application in corn soup were studied. The main objectives of this this research were to evaluate salt reduction that could be achieved through emulsion and to obtain a stable emulsion with most applicable viscosity for corn soup. In research stage I, three different oil concentrations (23, 28, and 33%) with constant salt and stabilizers concentration were applied into the emulsions. The result showed that emulsion with 33% oil was significantly more viscous than the others, whilst emulsion with 23% oil was found to be less salty than the others (α=0.05). Emulsion with 28% oil content was chosen for research stage II due to appropriate saltiness and viscosity. In research stage II, different types and concentrations of thickening agent (1 and 2% tapioca; 0.1 and 0.2% xanthan gum), and emulsifier concentration (0.5, 1.0, and 1.5% Soy Protein Isolate) were applied into the emulsions with 28% oil. The viscosity and stability of emulsion were significantly affected by the concentration of stabilizers. Emulsion with 28% oil content, 0.1% xanthan gum and 0.5% SPI was applied into corn soup. As a result, 25% reduction in sodium chloride could be achieved without significantly decreasing saltiness.